PROPAGANDA SLOGANS AND THE REALITY IN THE USSR IN THE PERIOD OF N. S. KHRUSHCHEV'S REFORMS - V. N. Tomilin (Гуманитарные и юридические исследования)
The article considers the effectiveness of social and economic policy of the Soviet State in the final period of N.S. Khrushchev's political leadership. The novelty of the research is in the reference to documents of the Central Committee of the CPSU which have been found in the Russian State Archives of Contemporary History and are introduced into scientific circulation for the first time. It is also in the analysis of the consumption level of different urban and rural population groups of the USSR based on the results of the 1962 budget survey. The relevance of this topic is determined by the tasks of the Russian State to solve the problem of equal opportunities for various categories of the population to satisfy their material and spiritual needs.